2013
DOI: 10.1089/ten.tea.2012.0742
|View full text |Cite
|
Sign up to set email alerts
|

Differential Morphology and Homogeneity of Tissue-Engineered Cartilage in Hydrodynamic Cultivation with Transient Exposure to Insulin-Like Growth Factor-1 and Transforming Growth Factor-β1

Abstract: Successful tissue-engineering strategies for cartilage repair must maximize the efficacy of chondrocytes within their limited life span. To that end, the combination of exogenous growth factors with mechanical stimuli holds promise for development of clinically relevant cartilage tissue substitutes. The current study aimed to determine whether incorporation of transient exposure to growth factors into a hydrodynamic bioreactor system can improve the functional maturation of tissue-engineered cartilage. Chondro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
(53 reference statements)
1
10
0
Order By: Relevance
“…TGF‐β1 stimulates in vitro chondrogenesis of chondrocytes, synovial lining and bone marrow‐derived MSCs activity . Diao et al, have demonstrated the promising role of TGF‐β1 in rabbits and showed enhanced repair of cartilage defects.…”
Section: Stimulation Factors Required For Cartilage Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF‐β1 stimulates in vitro chondrogenesis of chondrocytes, synovial lining and bone marrow‐derived MSCs activity . Diao et al, have demonstrated the promising role of TGF‐β1 in rabbits and showed enhanced repair of cartilage defects.…”
Section: Stimulation Factors Required For Cartilage Tissue Engineeringmentioning
confidence: 99%
“…This highlights the importance of IGF for growth and development. The role of IGF‐1 has been extensively studied with respect to cartilage repair and considered as an essential mediator for cartilage homeostasis and metabolism due to its capability to promote the chondrocyte survival and proliferation, induce chondrogenic differentiation and stimulate proteoglycan synthesis . IGF‐1 have shown induction of a number of anabolic effects and decreases catabolic responses, when added to monolayer or explant cultures of normal articular cartilage from a variety of species .…”
Section: Stimulation Factors Required For Cartilage Tissue Engineeringmentioning
confidence: 99%
“…IGF-I presents structural and functional analogies to insulin and is ineolved in growth and development. IGF-I is successfully used in tissue-engineering for cartilage repair and its homeostatic control was demonstrated; in fact, in cell cultures continuously stimulated by IGF-I or TGF-~l the massive growth factor leftovers in the environment down regulates the expression of the associated receptors (8).…”
Section: Discussionmentioning
confidence: 99%
“…IGF-I and -II are known to stimulate proliferation and proteoglycan synthesis in cultured chondrocytes (8).…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow aspirate has many essential growth factors needed for chondrocyte growth, and its constituents have been evaluated earlier7. Human chondrocytes proliferate at a faster rate without dedifferentiation in the presence of such individual growth factors than FBS9.…”
mentioning
confidence: 99%